The role of phytogenic feed additives in growth and immune response in livestock production: a global systematic review - Ntsongota, Zanoxolo; Ikusika, Olusegun; Jaja, Ishmeal Festus (Frontiers in Animal Science, 2025)
Phytogenic feed additives in livestock production, particularly in addressing their impact on growth and the immune response within the sector, are very important in modern agriculture. Therefore, the objective of this systematic review is to critically assess the current evidence on the impact of phytogenic feed additives on growth performance and immune response in livestock species. A systematic literature search was conducted according to the PRISMA guidelines. The searches were performed in multiple academic databases, Scopus, ScienceDirect, Web of Science and EBSCOhost (Academic Search Ultimate, AGRICOLA, and MEDLINE with full text), covering the period from January 1, 2010 to December 31, 2024. Among the 104 research papers downloaded, 20 were included and analysed directly in this study. The phytogenic feed additives identified in this study include essential oils, mango leaves, rosemary oils, turmeric, black cumin, propolis, thyme, Achyranthes, Lycium, Ajwain, Chenopodium, the phytoncide Dialium guineense, and Salix alba extracts. The results show that in poultry, typical improvements in body weight gain or average daily weight gain range from 5 to 13%, while lambs show some of the strongest responses, with growth increases of up to 30%. In pigs, benefits are more evident under disease or stress conditions, highlighting the health-supporting role of phytogenic feed additives. Rabbits respond moderately, particularly at optimal doses of bioactive-rich supplements such as propolis. In cattle, growth improvements are consistent but modest, suggesting that phytogenic feed additives function more as complements than primary growth promoters. A key theme across all species is the importance of dose–response optimization. Many phytogenic feed additives demonstrate nonlinear effects, where low-to-moderate inclusion levels increase growth, but excessively high levels either provide no additional benefit or impair feed efficiency. Additionally, the immunomodulatory potential of phytogenic feed additives appears to be strongest in monogastric species (poultry, pigs, and rabbits), where rapid immune responses are critical to productivity. Evidence from numerous livestock studies suggests that phytogenic feed additives are effective alternatives to traditional antibiotic growth promoters.